ANALISIS KESALAHAN BERBAHASA PADA ANAK USIA 2-3 TAHUN DI LIHAT DARI TATANAN FONOLOGI - Dariah Dariah; Irma Hanifah Sholihah; Via Nugraha (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
In teaching first language, the child is able to master the language by imitating what their mother says. Through their mother's mimic activity, the child is able to develop their language and knowledge of the structure and patterns of their mother tongue. In addition, the language controlled by the child resulting from the imitation of their mother tongue is not good and true in accordance with the rules of the Indonesian language. This is what causes errors in language of young learners. Such language errors can be eliminated by instilling good and proper language habits by both mother and family. In addition, children can be trained from an early age so that the language is not deviant. In the process of language development of children, speech language errors are included in the discussion of error analysis in phonology. A speech error is an error pronouncing the word so that it deviates from the raw speech. The aims of this studies are  to determine the errors of language in young learners and what words are the language pronunciation itself. The research design are: (1) the initial stage is the preparation stage to identify and search the literature study, especially with reference to related journals. (2) after the problem is identified and the basics of literature study are collected, the next stage conducts data collection with direct observation or observation. (3) after collected, recorded, documented, then analyzed by utilizing existing sources. (4) evaluate to get observation data to be used as a research result.